BONE HEALTH SURVEILLANCE AMONG AT-RISK CHILDREN AND ADOLESCENTS IN KUCHING, SARAWAK, MALAYSIA - Cheng, Hooi Peng (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Chronic health conditions impose poor bone health due to underlying inflammatory conditions, reduced weightbearing activity and pubertal delay. METHODS This prospective study was conducted as the pilot project for bone health surveillance among at-risk children and adolescents followed up by a multidisciplinary team from Paediatrics Department, Sarawak General Hospital from January to February 2024. A bone health screening questionnaire was administered, followed by a physical examination, and biochemical and radiological investigation. CASE A total of sixteen subjects (6 males, 10 females) with a mean age of 10.7 ± 2.74 years were recruited. Four subjects had primary bone disorders, while another 8 subjects (50.0%) had exposure to glucocorticoids for the management of various condition including systemic lupus erythematous (2 subjects, 12.5%), juvenile dermatomyositis (2 subjects, 12.5%), juvenile idiopathic arthritis (1 subjects, 6.3%), ANCA vasculitis (1 subject, 6.3%), autoimmune hepatitis (1 subject, 6.3%) and acute lymphoblastic leukaemia (1 subject, 6.3%). Only half of the subjects elicited adequate dairy consumption and took vitamin D supplements in the form of cholecalciferol or alfacalcidol. Sedentary lifestyle was observed in two thirds of the subjects. The physical stigmata of bone fragility disorders were present in 4 patients, and they had genetic confirmation of osteogenesis imperfecta. Five subjects (31.3%) had fracture of long bones, as well as osteoporosis. Bone-active therapy with bisphosphonate had commenced in three patients. Serum 25-hydroxy vitamin D and parathyroid level were examined in 5 subjects and 2 subjects were detected to have vitamin D deficiency. Four subjects (25.0%) displayed vertebral fractures. Overall, the mean areal bone mineral density Z- scores were -2.78 ± 1.74 for hip, -1.87 ± 1.71 for lumbar spines and -3.07 ± 2.16 for total body less head. CONCLUSION Bone health screening among the children and adolescents vulnerable to osteoporosis should be imparted as the standard of care.